Aaron Ember and the Establishment of Egypto-Semitic Phonological and Lexical Comparison (Part I) - Takács, Gábor (Acta Orientalia Vilnensia, 2005)
Institute of Linguistics, Hungarian Academy of ScienceThe paper evaluates the Lebenswerk of Aaron Ember, one of the greatest figures of Egypto-Semitic linguistic comparison, accompanied by an evaluation and a detailed analysis of his etymological suggestions in the light of recent progress in Semito-Hamitic comparative linguistics. He was known as American Egyptologist and Semiticist of Johns Hopkins University. He was born in Tulnas (Kovno) of Lithuania in 1878. The 80th anniversary of his tragical and premature end (1926) represents the proper time when Ember’s memory may be revived and his etymological research may gain a worthy appraisal. It is all the more actual since the so-called “old school” (or trend) of Egypto-Semitic comparative phonology, which he himself symbolized in the first decades of the 20th century, is nowadays undeservedly forgotten. It is hoped that the present paper revives the interest in an extremely productive and once influential trend of Semito-Hamitic linguistics, to which Egyptian historical linguistics until now owes so much.